The application of the BOPPPS model in the ward rounds of nurses’ standardized training in Southwest China: a mixed methods study - Shen, Ying (Frontiers in Medicine, 2024)
Background Teaching ward rounds are the main teaching method used to develop clinical skills in standardized nursing training. However, the existing methods lack of cultivation of comprehensive ability and humanistic care for nurses, cannot meet the requirements of standardized training for nurses. BOPPPS (bridge-in, objective, pre-assessment, participatory Learning, post-assessment, and summary) is a student-centered teaching model that has been proven to enhance classroom teaching effectiveness. Therefore, the BOPPPS model was applied and its effectiveness in standardized nursing training was evaluated. Methods In total, 260 nursing students were randomly allocated to two groups: the experimental group used the BOPPPS model and the control group used the traditional teaching model. This study used a mixed quantitative and qualitative research method to evaluate the effectiveness of the BOPPPS model. Results The quantitative results were as follows: no significant difference in baseline scores was observed between the two groups before training. After training, the theory and practical scores in the experimental group were significantly higher than that of the control group. Similarly, students in the experimental group presented higher comprehensive ability scores than their counterparts. The students in the experimental group also exhibited higher satisfaction compared to the control group, while there was no difference in teacher satisfaction scores between the two groups (p = 0.323). Qualitative data showed that the vast majority of nurses and teachers agreed on the value of BOPPPS training. Conclusion Compared to traditional teaching methods, the BOPPPS model was more effective in standardized nursing training. We recommend applying the BOPPPS model to nursing training.